On the morphology and systematics of Bembecia jakuta (Herz, 1903) (Lepidoptera, Sesiidae) - Oleg G. Gorbunov (Acta Biologica Sibirica)
The description and illustrations of Bembecia jakuta (Herz, 1903) are presented herein. To stabilize the species epithet, clarify the taxonomic status, and define the type locality of this under-researched species of clearwing moths (Lepidoptera, Sesiidae) within the Palearctic region, a neotype is designated. A comprehensive analysis of the external morphology, along with the examination of the male genitalia, indicates that this species is closely related to B. aktashica O. Gorbunov, 2018; however, it exhibits distinct differences in the coloration of certain body parts and the configuration of the transparent areas of the forewing. Furthermore, these two species display minor variations in the structure of the male genitalia. The female, host plants, and biological characteristics of the larvae remain unidentified.